The Effectiveness of Swimming Intervention and Supplementary Feeding on the Growth of Malnourished Children - Risa Arina Zakiyah; Nurul Pujiastuti; Andi Hayyun Abiddin (Health Gate, 2026)
Malnutrition has remained a public health issue both regionally and globally. This condition resulted from inadequate nutritional intake, both in terms of quality and quantity, as well as health problems that interfered with the absorption and utilization of nutrients. This study aimed to analyze the effectiveness of swimming intervention and supplementary feeding on the growth of malnourished children in Kepanjenkidul District. The research employed a quantitative method with a pre-experimental one-group pretest-posttest design, conducted in Kepanjenkidul District, Blitar City, from January to March 2025. The sample consisted of 20 respondents selected using purposive sampling. Data were collected using a digital scale, stadiometer, observation forms, and questionnaires. The analysis was carried out using univariate and bivariate methods with a paired t-test statistical analysis. The results of the study showed that there was a difference in growth status before and after the swimming intervention, with a p-value of 0.000. There was no difference in weight before and after the swimming intervention, with a p-value of 0.042. There was a significant difference in the effectiveness of the swimming intervention combined with supplementary feeding, with a p-value of 0.000. This study contributed to the development of knowledge in the field of child health and nutrition and served as a reference for future research regarding interventions for malnourished children.